(untitled) (Polis (Santiago), 2018)
This article reveals my intent as educator to provoke new thinking from the new paradigm, considering my personal and professional intentions, and finally considering social intentions that in this case are evident in my research about the metaphorical preschool emergency of a chilean and brazilian infant. From this approach and the encounters with preschoolers in the classroom, I propose an alternative approach towards the education for this century.